¿Es realmente posible otro mundo? O el lema de la Revolución Francesa reconsiderada 1 - Wallerstein, Immanuel (2006)
This text was prepared for the UNESCO CERES Conference Facing social transformations in the 21st century. A conference on inequality, pluralism and environment, held in 29-30 June 2006 at the University of Utrecht. After reviewing the structural crisis of the economy and the capitalistic world in the last few years, and after reinforcing the set of guiding questions, I. Wallerstein wonders if another world is really possible? And if so, how should it be? And how could we build it? His replies deal with three key issues: pluralism, the environment and inequality.